Taxonomic revision of the sub-Saharan Anthidiellum Cockerell (Apoidea: Megachilidae: Anthidiini) - Eardley, Connal (Zootaxa, 2018)
The Afrotropical species of the genus Anthidiellum Cockerell are revised. There are twelve species in two distinct subgenera; Pycnanthidium and Chloranthidiellum. An early record of Anthidiellum sensu stricto from Africa resulted from a misidentification. Two new species are described, Anthidiellum (Chloranthidiellum) pamae and Anthidiellum (Pycnanthidium) somaliense. Anthidiellum eritrinum is moved from the nominative subgenus to Chloranthidiellum, and a key for the identification of both sexes of the species is given. The species are redescribed with illustrations of male terminalia for most species, which have not been published before, and colour photographs. Four names are held in abeyance because their identity, and therefore status as valid species, is uncertain. They are Anthidiellum tegwaniense (Cockerell); Anthidiellum bulawayense Mavromoustakis; Anthidiellum nigripes (Friese) and Anthidiellum orichalciscopatum (Strand). They are here tentatively presumed to be junior synonyms of Anthidiellum zebra Friese.